Sustainable Community Development Step 1: Get Stakeholder Agreement about Implementing a Sustainability Program - Mickie E. Swisher; Sandra Rezola; James Sterns (EDIS)
This document explains how to recruit and bring together stakeholders before implementing a sustainability program. This document is FCS7214-Eng, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: September 2003.